Web discussions on cardiovascular diseases: pre-COVID-19 evaluation and impact of the COVID-19 pandemic - Web listening analysis in the Italian population - Isabella Cecchini; Matteo Biroli; Katia Massaroni; Emanuela Folco; Maria Rita Montebelli; Giuseppe Ciancamerla; Daniela Giudice; Roberto Franco Enrico Pedretti; Paolo Magni (BMC, 2024)
Abstract Background Web discussions on health issues are becoming very relevant in the general public. In this context, little information is available regarding cardiovascular diseases, which remain the first cause of morbidity, disability and mortality worldwide. The central objective of the study was to conduct a Web listening analysis on discussions about cardiovascular diseases in Italy, comparing the data relative to the 2-year pre-COVID-19 pandemic period with those collected during the COVID-19 pandemic lockdown (March-July 2020), with quantification of conversations on cardiovascular disease and Web-based discussions and specific evaluation of COVID-19 lockdown impact. Methods A retrospective Web listening analysis using publicly available data was conducted, using validated methods that allow to estimate cardiovascular disease awareness. Digital sources were identified to retrieve data (Italian language), relevant to cardiovascular disease topics. Data were analysed by Google Trends methodology and the Digital Intelligence Platform Brandwatch. Natural Language Processing algorithms enabled comparative analysis, topic detection, classification, leading to a 279,790-item dataset. Results News channels and Twitter were the most important platforms feeding cardiovascular disease information. Facebook was mostly relevant for information sharing. In the pre-COVID-19 period, cardiovascular disease ranked 5th among main health issues (vaccines, tumors, influenza, diabetes) on the Web, and the most discussed cardiovascular disease themes were symptoms/diagnosis (34%), treatments (20%), disease causes/triggers (11%), disease information (9%), quality of life (8%). Conversations on cardiovascular disease prevention were marginal (5%). The COVID-19 pandemic lockdown strongly impacted on discussed topics; novel themes emerged: hospitalization, death risk/occurrence, greater cardiovascular disease risk. Discussions on cardiovascular disease prevention remained marginal (4%). COVID-19 pandemic increased fear of severe COVID-19 among patients with cardiovascular disease and worsened quality of relationship/contact with physicians. Conclusions A limited awareness of cardiovascular disease and their prevention was observed before and during the COVID-19 pandemic. Patients/caregivers need more information and contact with physicians, as it emerged during COVID-19 pandemic. It is urgent to promote novel prevention strategies and to engage people leveraging digital channels and social media. Graphical Abstract